E-Learning Development with the ICARE Learning Flow in the Learning Materials Development Course in the Educational Technology Study Program, Ganesha University of Education - Alexander Hamonangan Simamora; I Gusti Agung Ngurah Trisna Jayantika; I Kadek Suartama (Lembaga Bale Literasi, 2026)
Digital transformation in higher education requires innovation in electronic learning content (e-learning) so that it is not just administrative or monotonous that triggers digital fatigue. This research aims to develop and test the feasibility and effectiveness of e-learning content based on the ICARE (Introduction, Connect, Apply, Reflect, Extend) flow in the Teaching Material Development course at the Educational Technology Study Program of FIP Undiksha. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The feasibility of the product is tested through expert review and user trials, while its effectiveness is analyzed using the one sample t-test after meeting the prerequisite tests for normality and homogeneity. The results of the validity test showed that the product was categorized as very good in the media (96%), material (91.42%), and individual trials (92.6%), as well as in the good category in the design (82.5%) and small group tests (85.5%). The data on student learning outcomes were declared to be distributed normally (Sig. 0.114 > 0.05) and homogeneous (Sig. 0.560 > 0.05). The results of the analysis of the one sample t-test obtained a significance value of 0.001 (< 0.05), which proves that there is a significant increase in student learning outcomes compared to the reference value of 75 after utilizing the integrated e-learning ICARE flow. The advantage of this model lies in the Apply and Extend phases which successfully trigger students' emotional, cognitive, and creative thinking skills through social constructivism-based problem-solving. This study concludes that ICARE-based e-learning is feasible and effective to be used as a prototype of interactive and adaptive digital learning content in higher education.